The Hegemony of Heritage : Ritual and the Record in Stone - Stein, Deborah L., 1975- (Book collections on Project MUSE., 2018)
"The Hegemony of Heritage makes an original and significant contribution to our understanding of how architectural objects and societies' relationship to the built environment change over time. Using the pairing of two living medieval monuments in Southern Rajasthan--the Ambika Temple in Jagat, Rajasthan, and the Ékalingji Temple Complex in Kailaspuri--the author underscores many aspects of practice and avoids focusing simply on their divergent sectarian affiliations or patronage structures. This book offers new and extremely valuable questions about these important monuments, such as the entangled politics of antiquity and whether a monument's ritual record is affirmed as continuous and hence hoary, or dismissed as discontinuous or reinvented through various strategies. The Hegemony of Heritage engages theoretical constructs with the richness of ethnographic description and asks us to rethink notions such as archive and text through the filter of sculpture and mantra."--Provided by publisher